ASSESSING EFFECTS OF EQUISETUM RAMOSISSIMUM EXTRACT ON HEMATOLOGICAL AND SERUM BIOCHEMICAL PARAMETERS IN PREGNANT SPRAGUE-DAWLEY RATS - Alebous, Hana Dawood; Hudeb, Arwa Ali; Sober, Suzanne Ali; Gray, Rosianna; Johnson, Margaret Dean (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: As a medicinal herb, Equisetum ramossisemum has been utilized for centuries as a diuretic and has beenrecommended for different disorders. The aim of this study was to investigate the maternal toxicity of aerial parts of Equisetumramosissimum extract on pregnant Sprague-Dawley rats.Methods: Females were mated and the coupling time was recorded at gestation day 0– E0. Four experimental groups I, II, III, andIV, received daily gavage doses of 0 mg, 500 mg, 250 mg, and 125 mg/kg, respectively, of Equisetum ramosissimum extract.Pregnant rats were observed for mortality and toxicological effects during daily treatment. On day E20, samples of blood werewithdrawn from the retro-orbital sinus under light ether anaesthesia for haematological and clinical chemistry examinations.Results: Data analyses detected significant differences in biochemical and haematological parameters between the control group andother groups receiving extract.Conclusion: This study constitutes a first approach to defining adverse effects of using Equisetum ramosissimum as a medicinalplant during pregnancy. Daily gavage doses of Equisetum ramosissimum extract produced significant differences in biochemical andhaematological parameters in pregnant Sprague-Dawley rats as compared to the control group.